Modified NWChem Code Utilizes Supercomputer Parallelization - Barney, Linda (Scientific Computing, 2016)
This is the first in a series of articles, told from the perspective of individuals who are updating codes, that describes changes various national laboratories and scientific research centers are making to improve code optimization and parallelization in order to reduce time to discovery. NWChem is a widely used open source software computational chemistry package that includes both quantum chemical and molecular dynamics functionality.